Kształtowanie się właściwości fizycznych gleb murszowych obszarów łąkowych i leśnych w różnym stopniu przesuszonych = Evolution of physical properties of mucky peat soils in differently dried forest and meadow areas - Szulc, Agnieszka; Bogacz, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The study was conducted on forest and meedow areas located on the border parts of Odra marginal valley in Przedmoście locality of Lower Silesia region. The aim of reasearch was comparative analysis of physical properties of soil and estimating the impact of muck process on organic horizon retention.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)